Trajectory of Parvalbumin Cell Impairment and Loss of Cortical Inhibition in Traumatic Brain Injury. (1st December 2016) - Hsieh, Tsung-Hsun; Lee, Henry Hing Cheong; Hameed, Mustafa Qadir; Pascual-Leone, Alvaro; Hensch, Takao K; Rotenberg, Alexander
Abstract: Many neuropsychiatric symptoms that follow traumatic brain injury (TBI), including mood disorders, sleep disturbance, chronic pain, and posttraumatic epilepsy (PTE) are attributable to compromised cortical inhibition. However, the temporal trajectory of cortical inhibition loss and its underlying mechanisms are not known. Using paired-pulse transcranial magnetic stimulation (ppTMS) and immunohistochemistry, we tracked functional and cellular changes of cortical inhibitory network elements after fluid-percussion injury (FPI) in rats. ppTMS revealed a progressive loss of cortical inhibition as early as 2 weeks after FPI. This profile paralleled the increasing levels of cortical oxidative stress, which was accompanied by a gradual loss of parvalbumin (PV) immunoreactivity in perilesional cortex. Preceding the PV loss, we identified a degradation of the perineuronal net (PNN)—a specialized extracellular structure enwrapping cortical PV-positive (PV+) inhibitory interneurons which binds the PV+ cell maintenance factor, Otx2. The trajectory of these impairments underlies the reduced inhibitory tone, which can contribute to posttraumatic neurological conditions, such as PTE. Taken together, our results highlight the use of ppTMS as a biomarker to track the course of cortical inhibitory dysfunction post-TBI. Moreover, the neuroprotective role of PNNs on PV+ cell function suggests antioxidant treatment or Otx2 enhancement as a promising prophylaxis for post-TBI symptoms.